Electrochemical and physicochemical properties of small phosphonium cation ionic liquid electrolytes with high lithium salt content. Issue 14 (4th March 2015) - Girard, G. M. A.; Hilder, M.; Zhu, H.; Nucciarone, D.; Whitbread, K.; Zavorine, S.; Moser, M.; Forsyth, M.; MacFarlane, D. R.; Howlett, P. C.
Abstract : A novel phosphonium ionic liquid as potential candidate for lithium battery electrolytes. Abstract : Electrolytes of a room temperature ionic liquid (RTIL), trimethyl(isobutyl)phosphonium (P111i4 ) bis(fluorosulfonyl)imide (FSI) with a wide range of lithium bis(fluorosulfonyl)imide (LiFSI) salt concentrations (up to 3.8 mol kg −1 of salt in the RTIL) were characterised using a combination of techniques including viscosity, conductivity, differential scanning calorimetry (DSC), electrochemical impedance spectroscopy (EIS), nuclear magnetic resonance (NMR) and cyclic voltammetry (CV). We show that the FSI-based electrolyte containing a high salt concentration ( e.g. 1 : 1 salt to IL molar ratio, equivalent to 3.2 mol kg −1 of LiFSI) displays unusual transport behavior with respect to lithium ion mobility and promising electrochemical behavior, despite an increase in viscosity. These electrolytes could compete with the more traditionally studied nitrogen-based ionic liquids (ILs) in lithium battery applications.